2019
DOI: 10.1021/acs.jpcc.9b04357
|View full text |Cite
|
Sign up to set email alerts
|

Electrocoalescence Criterion of Conducting Droplets Suspended in a Viscous Fluid

Abstract: Coalescence of conducting droplets dispersed in an immiscible medium can be facilitated by an electric field. However, droplets recoil promptly after contact in sufficiently high electric fields if the cone angle between droplets exceeds a critical value. To elucidate the critical condition for droplet coalescence, the behavior of two suspended droplets after contact with a direct current electric field is studied. It is shown that the critical angle is determined not only by the droplet geometry but also cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 40 publications
(84 reference statements)
1
22
0
Order By: Relevance
“…The radii of droplets gradually increase with time after experiencing continual coalescence. The critical electric field strength for droplet coalescence gradually decreases as the droplet radius increases . Therefore, when exceeding the critical electric field strength, large droplets no longer coalesce but form short droplet chains from the right electrode plate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The radii of droplets gradually increase with time after experiencing continual coalescence. The critical electric field strength for droplet coalescence gradually decreases as the droplet radius increases . Therefore, when exceeding the critical electric field strength, large droplets no longer coalesce but form short droplet chains from the right electrode plate.…”
Section: Resultsmentioning
confidence: 99%
“…The critical electric field strength for droplet coalescence gradually decreases as the droplet radius increases. 39 Therefore, when exceeding the critical electric field strength, large droplets no longer coalesce but form short droplet chains from the right electrode plate. However, the short droplet chain is unstable and disintegrates after a while.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…After that glycerol molecules had moved closer and linked together. Finally, they had precipitated to the bottom [14][15][16]. Additionally, AC was applied to reduce corrosion of electrodes that can impact to efficiency loss of current transfer [17].…”
Section: Electrocoagulation Separation Processmentioning
confidence: 99%
“…Lu et al 16 found that the critical cone angle gradually increases and then remains at 27° as the viscosity of droplet increases. Luo et al 17 experimentally showed that the critical cone angle reduces with the increase in conductivity of droplets or concentration of surfactant. Nevertheless, a few scholars considered that the charge transfer is the fundamental mechanism of droplet non‐coalescence.…”
Section: Introductionmentioning
confidence: 99%